Consequences of regional economic integration: theoretical aspects and practice of the EAEU (Journal of Economic Research & Business Administration, 2018)
The economic consequences of regional integration are significant to the debate in Europe, theUnited States and other countries around the world. The purpose of this study is to identify, on the basisof research papers by foreign and domestic scientists, the positive and negative consequences of theregional economic integration and the assessment of their manifestation in the economy of the EAEUcountries.The scientific and practical significance of the work is as follows. Despite many years of experiencein world economic integration, there is still no consensus on the prevalence of positive or negative effectsof integration. We have studied and summarized a large theoretical and practical material on theconsequences of the regional integration and analyzed data on the member countries of the EAEU. Theanalysis showed that membership in the EAEU has not yet shown significant positive effects for partnercountries. The dynamics and trends in the growth of integration effects in the EAEU cause some concern.However, the reasons for these processes lie not in the group itself, but rather in the unfavorable situationon the world market. The fall in the world market for oil and gas prices and the impact of currencyfluctuations on the market. Of course, all this has affected the domestic economic situation in the partnercountries. Since 2017, there has been a recovery in economic growth. In connection with the growthof the economy for all countries will be characterized by the restoration of consumer demand. One ofthe factors of growth will be investment activity in the EAEU states. Conditions for increasing the investmentactivity of the private sector will be created, including through price stabilization. Thus, summingup the results of our research, we hope that it will contribute to the scientific literature on the problemsof regional economic integration, proving a new approach to determining its effects. Our results showthat economic integration is not a zero-sum game and can be mutually beneficial for partner countries.